Clay fills proceedings of the conference held at the Institution of Civil Engineers, 14-15 November 1978. (Institution of Civil Engineers, 1979)
Following an opening address by A.M. Muir Wood, this work focuses on stress-deformation and strength characteristics of a compacted shale, roadwork fills, volume change of compacted clay fill, and trafficability studies on wet clay.